2002
DOI: 10.1677/joe.0.1730507
|View full text |Cite
|
Sign up to set email alerts
|

Plasma growth hormone and growth hormone-binding protein during development in the marsupial brushtail possum (Trichosurus vulpecula)

Abstract: Plasma concentrations of growth hormone (GH) were measured in the brushtail possum (Trichosurus vulpecula) pouch young from 25 through to 198 days post-partum (n=71). GH concentrations were highest early in pouch life (around 100 ng/ml), and thereafter declined in an exponential fashion to reach adult concentrations (10·8 1·8 ng/ml; n=21) by approximately 121-145 days post-partum, one to two months before the young is weaned. Growth hormone-binding protein (GHBP), which has been shown to modify the cellular ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
1

Year Published

2003
2003
2019
2019

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 43 publications
0
7
1
Order By: Relevance
“…We have previously reported that plasma GH concentrations in the possum pouch young are very high early in life but then decline to reach adult levels by about 96-120 days post-partum (Saunders et al 2002). In the present study on precisely aged pouch young, plasma GH concentrations remained elevated above those in the adult until 125 days post-partum, even though they had declined from those seen in younger animals.…”
Section: Discussioncontrasting
confidence: 59%
See 4 more Smart Citations
“…We have previously reported that plasma GH concentrations in the possum pouch young are very high early in life but then decline to reach adult levels by about 96-120 days post-partum (Saunders et al 2002). In the present study on precisely aged pouch young, plasma GH concentrations remained elevated above those in the adult until 125 days post-partum, even though they had declined from those seen in younger animals.…”
Section: Discussioncontrasting
confidence: 59%
“…Our results for GHR and IGF-I, which are negatively correlated with plasma GH, suggest that the possum liver is resistant to GH early in pouch life, possibly because GHR expression is low. In support of this explanation, plasma GH-binding protein concentration, which correlates with liver GHR levels in eutherian mammals (Mulumba et al 1991, Ambler et al 1992, is also low early in pouch life (days 45-87) but then increases more than 3-fold by about 120 days post-partum (Saunders et al 2002). In eutherian mammals, the fetal liver is relatively insensitive to GH and only post-natally does GH become an important regulator of hepatic IGF-I production.…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations